2017
DOI: 10.1038/modpathol.2016.179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of recurrent mutational events in anorectal melanoma

Abstract: Anorectal melanoma is a rare disease that carries a poor prognosis. To date, limited genetic analyses confirmed KIT mutations as a recurrent genetic event similar to other mucosal melanomas, occurring in up to 30% of anorectal melanomas. Importantly, a subset of tumors harboring activating KIT mutations have been found to respond to c-Kit inhibitor-based therapy, with improved patient survival at advanced tumor stages. We performed comprehensive targeted exon sequencing analysis of 467 cancer-related genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 60 publications
13
41
0
1
Order By: Relevance
“…Mutations in BRAF were seen but these were not the driver V600 mutations described in cutaneous melanoma (Table 1). Similar to other studies 7, frequent mutations in KIT were found, especially in the vulvovaginal and anorectal subtypes. In these two groups of patients, the KIT mutations were comutated with NF1 in 32% of the samples.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Mutations in BRAF were seen but these were not the driver V600 mutations described in cutaneous melanoma (Table 1). Similar to other studies 7, frequent mutations in KIT were found, especially in the vulvovaginal and anorectal subtypes. In these two groups of patients, the KIT mutations were comutated with NF1 in 32% of the samples.…”
Section: Discussionsupporting
confidence: 89%
“…The other two patients carried mutation R625C in SF3B1 , and one variant R625S. A recent targeted sequencing of 15 anorectal mucosal melanoma patients described five patients with the identical SF3B1 R625 mutation, confirming our findings 7. WES in cutaneous melanoma found only a very low frequency of SF3B1 R625H/C mutations, 2/231 cutaneous patient samples 14.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations